AngloModern : painting and modernity in Britain and the United States - Wolff, Janet (Cornell University Press, 2003)
In a masterly book on the sociology of modernism, Janet Wolff explores work that was primarily realist and figurative and investigates the processes by which art fell by the wayside in the post-war period.